Direct oral anticoagulants and advanced liver disease: A systematic review and meta‐analysis. (27th September 2020) - Menichelli, Danilo; Ronca, Vincenzo; Di Rocco, Arianna; Pignatelli, Pasquale; Marco Podda, Gian
Abstract: Background: Direct oral anticoagulants (DOACs) are recommended for stroke prevention in patients with atrial fibrillation (AF) or for treatment of deep vein thrombosis, although some concerns about safety and efficacy were raised on the use of these drugs in patients with advanced liver disease (ALD). We want to investigate the association of DOACs use with the bleeding and ischaemic risk. Material and Methods: We performed a systematic review and metanalysis of clinical studies retrieved from PubMed (via MEDLINE) and Cochrane (CENTRAL) databases addressing the impact of DOACs therapy on bleeding events including intracranial haemorrhage (ICH), gastrointestinal and major bleeding. Secondary end points were all‐cause death, ischaemic stroke/systemic embolism (IS/SE) and recurrence/progression of vein thrombosis (rDVT). Results: 12 studies were included in the meta‐analysis: a total of 43 532 patients with ALD or cirrhosis, of whom 27 574 (63.3%) were on treatment with DOACs and 15 958 were in warfarin/low molecular weight heparin. DOACs reduced the incidence of major bleeding by 61% (pooled Hazard Ratio [HR] 0.39, 95% Confidence Interval [CI] 0.21‐0.70), ICH by 52% (HR 0.48, 95% CI 0.40‐0.59), while no difference in the reduction of any and gastrointestinal bleeding were observed. DOACs reduced also rDVT by 82% (HR 0.18, 95%CI 0.06‐0.57), but did not reduce death and IS/SE. No difference was shown according to oesophageal varices and Child Pugh score in the meta‐regression analysis between warfarin/heparin and DOACs performed on each outcome. Conclusions: DOACs are associated with a lower incidence of bleeding and may be an attractive therapeutic option in patients with cirrhosis.